Tip-on-Tip Scapular (TOTS) Flap for Reconstruction of Combined Palatectomy and Rhinectomy Defects - Bartholomew, Ryan A.; Zenga, Joseph; Lin, Derrick T.; Deschler, Daniel G.; Richmon, Jeremy D. (Facial Plastic Surgery, 2018)
Combination anterior palatectomy and rhinectomy defects result in complete loss of midface and nasal support and present a significant reconstructive challenge. A novel use of the scapular tip free flap—the tip-on-tip scapula flap—was developed to provide both palatal repair and restoration of intrinsic nasal support. The scapular tip bone is split into a large proximal segment for the anterior palate and a smaller distal bone segment for nasal framework reconstruction. Two patients undergoing reconstruction of both total palatectomy and partial rhinectomy defects at a single academic tertiary care center were reviewed. In both cases, the larger proximal segment of the scapular tip flap, used for the palatal defect, was based on the angular artery. The distal bone segment, used for nasal framework repair, was vascularized in one of two ways. In the osteomyogenous serratus-scapular tip variant, the serratus arterial branch provided periosteal blood supply to the bone through a cuff of attached serratus muscle. In the split-scapular tip variant, the periosteum of the scapular tip was kept in continuity with the distal bone segment and fed through the periosteal vascular arcade from the angular branch. In both patients, the distal bone segment demonstrated robust intraoperative vascularity and both flaps healed without complication. Both patients were able to resume oral diets and had good nasal breathing.
Keywords: scapular tip flap; palatectomy; rhinectomy; reconstruction